Factors associated with complete discontinuation of medication among patients with schizophrenia in the year after hospital discharge. (April 2017) - Zhou, Yanling; Rosenheck, Robert; Mohamed, Somaia; Ning, Yuping; He, Hongbo
Abstract: Medication discontinuation is a major risk factor for relapse in schizophrenic patients. The present study investigated the rate and clinical correlates of complete medication discontinuation in the year after hospital discharge. Data collected from 236 schizophrenia patients who were prescribed anti-psychotics documented socio-demographic characteristics, symptom severity, insight, and attitudes towards medication in the week before their discharge and the experience of caregiver burden for their primary caregiver as recorded at the time of hospitalization. Follow-up telephones call one-year after discharge documented whether they were regularly taking prescribed psychotropic medication or not. Logistic regression analysis was used to investigate factors that were independently associated with medication discontinuation. Altogether 25.8% of the sample discontinued medication in the one-year after discharge. Logistic regression analysis showed that shorter duration of illness, lack of health insurance, and poor insight at the time of discharge were significantly associated with complete discontinuation of medication (p<0.05). Patients discontinued their medication within a year after psychiatric hospitalization which was associated with a lack of insurance coverage, less insight into their illness and shorter duration of illness. Interventions that strengthen patient engagement in treatment through insurance coverage and insight, fostered through psychoeducational intervention, may increase medication compliance. Highlights: Altogether 25.8% of the patients after psychiatric hospitalization discontinued medication in the one-year after discharge with risk factors of With risk factors of lack of insurance coverage, less insight into their illness and shorter duration of illness.